Glucose adsorption to chitosan membranes increases proliferation of human chondrocyte via mammalian target of rapamycin complex 1 and sterol regulatory element‐binding protein‐1 signaling. Issue 10 (3rd May 2017) - Chang, Shun‐Fu; Huang, Kuo‐Chin; Cheng, Chin‐Chang; Su, Yu‐Ping; Lee, Ko‐Chao; Chen, Cheng‐Nan; Chang, Hsin‐I
Abstract : Osteoarthritis (OA) is currently still an irreversible degenerative disease of the articular cartilage. Recent, dextrose (d ‐glucose) intraarticular injection prolotherapy for OA patients has been reported to benefit the chondrogenic stimulation of damaged cartilage. However, the detailed mechanism of glucose's effect on cartilage repair remains unclear. Chitosan, a naturally derived polysaccharide, has recently been investigated as a surgical or dental dressing to control breeding. Therefore, in this study, glucose was adsorbed to chitosan membranes (CTS‐Glc), and the study aimed to investigate whether CTS‐Glc complex membranes could regulate the proliferation of human OA chondrocytes and to explore the underlying mechanism. Human OA and SW1353 chondrocytes were used in this study. The experiments involving the transfection of cells used SW1353 chondrocytes. A specific inhibitor and siRNAs were used to investigate the mechanism underlying the CTS‐Glc‐regulated proliferation of human chondrocytes. We found that CTS‐Glc significantly increased the proliferation of both human OA and SW1353 chondrocytes comparable to glucose‐ or chitosan‐only stimulation. The role of mammalian target of rapamycin complex 1 (mTORC1) signaling, including mTOR, raptor, and S6k proteins, has been demonstrated in the regulation of CTS‐Glc‐increased human chondrocyte proliferation. mTORC1 signaling increased the expression levels of maturated SREBP‐1 and FASN and then induced the expressions of cell cycle regulators, that is, cyclin D, cyclin‐dependent kinase‐4 and ‐6 in human chondrocytes. This study elucidates the detailed mechanism behind the effect of CTS‐Glc complex membranes in promoting chondrocyte proliferation and proposes a possible clinical application of the CTS‐Glc complex in the dextrose intraarticular injection of OA prolotherapy in the future to attenuate the pain and discomfort of OA patients. Abstract : The adsorption of glucose onto the chitosan membranes increased human chondrocyte proliferation by activating mTORC1 signaling and then induced the expression of mSREBP‐1/FASN/cell cycle regulators (cyclin D and CDK‐4/6).